Sustitución parcial del nitrito de sodio por extracto de achiote y su influencia en la calidad de una salchicha de pollo - Párraga Quijije, Carlos Junior (2022)
The objective of this work was to infer the partial substitution of sodium nitrite by annatto extract (Bixa Orellana L.) on the microbiological, physical-chemical and sensory properties in a chicken sausage. For the physical-chemical variables, a DCA (Completely Random Design) with a single factor was applied, while for the microbiological variables a completely randomized block design (DBCA) was applied. The study factor was the powdered achiote extract in concentrations of 0.08%, 0.10%, 0.12%, 0.14% and 0.16% in the different study treatments. The results of the physicochemical variables did not comply with the parametric test (ANOVA), which is why the non-parametric Kruskal-Wallis test was carried out, where it was possible to identify that in the parameters of pH, acidity and residual nitrite treatment T2 (0, 10% annatto extract) obtained a higher significant incidence, in the same way in the microbiological analyzes it was determined that, for Mesophilic Aerobes, Escherichia Coli and Sataphylococcus Aureus in T2 treatment (0.10% annatto extract) reflected the best averages, this produce that the count of colony-forming units decreased on day 12 compared to the results initially obtained on day 0, complying with the standards of the NTE INEN 1338:2012 for both the physicochemical and microbiological requirements. Sensory analysis (hedonic scale) was performed on 75 untrained tasters and the results were analyzed using the Friedman test, where no significant differences were found between the treatments.